Rape in South Africa : the experiences of women who have been raped by a "known person" : a case study of women at a shelter in Johannesburg. - Spengler, Corey Sarana (My University, 2014)
Police statistics in South Africa show that the numbers of reported rape cases are growing annually and studies have shown that a large percentage of women are not reporting their rapes. My research looks at the experiences of women who were raped by a “known person” and were at the time of the research living in a shelter, either as a result of abuse or because they were homeless. Through standpoint theory I made use of my own rape experience as an opener into the area of research and as a tool in obtaining the respondents for my research. In-depth interviews were utilised in obtaining the detailed narratives from the women who took part in the research. The narratives were based on the women’s experiences of rape by a “known person”. Within the research a “known person” included, amongst others, family members, “boyfriends”, friends and intimate partners. The aim of my research was to provide insight into the experience of being raped and to show how for women it is a lived experience that affected the course of their lives. The narratives were linked to the greater theoretical context of rape in South Africa. This was done in order to highlight the extent of the influence that the rape experience has on the survivor’s life and the choices that they make. Overall, my research sought to give insight into the subject of rape in South Africa, in order to highlight the fact that rape goes beyond the statistics and to show how the women’s individual rape experiences shaped their lives. Within my research report I have highlighted the literature on rape, both globally and that which is specific to South Africa. The report then goes on to look at the theory of feminism, feminist standpoint theory, patriarchy as an element of feminism, stigma, rape myths or stereotypes and structure and agency. This is followed by an outline of the methodology used, an introduction to the research site and the detailed narratives of the respondents. This is all drawn together in the analysis chapter where the narratives are linked to both the literature and the theoretical framework. The conclusion summarises everything and notes the limitations, findings and the way forward for the research. My research could be criticised for the small number of respondents, however, due to the nature of the research topic, it was imperative to obtain very detailed data. My research also chose to focus on women from a low socio-economic background and all the respondents were from an African or mixed-race racial group. However, due to their own personal experience of rape, other women will still be able to relate to the respondents’ experience, due to the commonality of the violation of the female body. The narratives came from the respondents themselves and this increased the validity of the information. My own rape experience could have had both a positive and negative impact on my research. My rape story assisted in obtaining the respondents as well as in my understanding of the area of research, however, it could also have led to possible bias on my behalf as the researcher, and it is therefore acknowledged. My research was largely able to confirm what was found in the literature and it shows how a girl child who has been abused is more likely to be abused as an adult. It also focused on how the family was able to hide the abuse and keep the women from seeking the necessary help. It highlighted the power men held over women due to patriarchy and the role that virginity played for the respondents. The role of religion in the respondent’s post-rape experience was also looked at. Following on from my research there are areas that can be strengthened as well as areas for further research. One example of this was the interlinked issues that were raised regarding family, virginity and culture.
Keywords: Rape; South Africa; Shelters